Financial Performance Analysis of PT. Pertamina (Persero) in Comparison with Other Local and Global Oil & Gas Companies - Metharyanasari, Devy; Zen, Tuntun Salamatun (Journal of Business and Management, 2016)
Abstract.In recent years, as a developing country, Indonesia has been facing with several uncertainty conditions, such as political changes, government policies, increasing in population, and unstable economics growth. Indonesia’s economic growth shows that Indonesia’s GDP (Gross Domestic Product) was decline starting 912.52 billion US dollars in 2013 and continues to decline in 2015 was worth 861.3 billion US dollars. There are some factors that influenced Indonesia’s economic growth recently those are the presence and activity of business areas, such as manufacturers, pharmaceutical, telecommunications, property, banks, creative economics, mining, and many more. For mining areas, especially in oil & gas sectors, refers to Special Task Force for Upstream Oil and Gas Business Activities (SKK Migas) which is an institution that under the auspices of the Minister of Energy and Mineral Resources, said that this sector having a fluctuation growth since the world oil prices have been hit severely since early 2015. This caused a serious negative impact to oil and gas companies in the world, included Indonesia. Regarding to the declining world oil prices in early 2015, the problem causing disruption of business activities conducted by PT. Pertamina such as declining on generate sales. To know how does the financial performance recently, PT. Pertamina (Persero) will be compared to other local and global benchmark companies, which are PT. Medco Energi International, Chevron Corporation, and ConocoPhillips. The methods that will be used to analyze consists of Financial Ratio (Trend Analysis, Cross-Sectional Analysis, CAGR comparison), DuPont Analysis, and BUMN Scoring. In conclusion, according to the analysis that has been done, PT. Pertamina (Persero) obtain fluctuate results tend to decline in some ratios during 2011 – 2015, then there will be given the recommendation in order to improve the financial performance of PT. Pertamina (Persero) such as use operating efficiently and managing other costs and expenses also focus on generating more sales. There will a further research given to the company, which are using moody’s rating and measures company’s value by using valuation method.Keywords: PT. Pertamina (Persero); Financial Performance Analysis; Financial Ratios; DuPont Analysis; Oil & Gas Companies